Analysis of Rainfall and Runoff Flood Frequency Based on Statistical and Hydrological Models - Mohammed M. Ahmed; Abdul-Sahib T. Al-Madhhachi; Alaa M. Al-Lami (Civil Engineering Journal, 2026)
This study aims to design ten-hour rainfall and runoff storms using the Chicago, Weibull, and Gumbel models for periods of 2, 10, 25, and 100 years of the planned dam in the Makhoul Basin of northern Iraq. The design storms are based on thirty years of historical data on flow rates from Mosul Dam, Dukan Dam, the Greater Zab, and the Little Zab Streams, as well as rainfall data from stations in Kirkuk, Mosul, Baiji, and Tikrit, from 1994 to 2024. Intensity-duration-frequency curves, along with the Chicago method, were employed to design the rainfall storms. The planning of the Makhoul Dam Basin is influenced by the diverse characteristics of incoming water from multiple sources, including the Greater and Little Zab Streams and the Tigris River. The analysis indicates a significant increase in discharge volume for the 100-year return period at Mosul Dam, which has the highest discharge rate of 3,000 m³/s, while the maximum discharge at Dukan Dam does not exceed 800 m³/s. The study concludes that constructing the Makhoul Dam in the near future is essential for managing floods resulting from heavy rainfall and runoff exacerbated by climate change, particularly given the lack of control over the Greater Zab Stream.